Orthodox View on the 30th Anniversary of the Azerbaijan's "Contract of the Century" - Gubad Ibadoghlu (SSRN, 2024)
A 30-year period is sufficient to evaluate the place of the “Contract of the Century” in modern Azerbaijani history and its role in shaping the national economy. Although such evaluations are conducted periodically, we will attempt to conclude the assessment on the occasion of COP29, which Azerbaijan is hosting. This marks the 30th anniversary of the signing of the first contract, and provides a unique opportunity for both retrospective reflection and a forward-looking perspective, filled with hope and optimism for the future.
Keywords: 330; Azerbaijan; oil & gas sector; COP29; “Contract of the Century”; PSA; ACG; GDP; investment; exports; BP; SOCAR